1993
DOI: 10.1002/ajmg.1320470706
|View full text |Cite
|
Sign up to set email alerts
|

Mild Brachmann‐de Lange syndrome. Delineation of the clinical phenotype, and characteristic behaviors in a six‐year‐old boy

Abstract: Brachmann-de Lange syndrome (BDLS) is a rare multiple congenital anomaly/mental retardation (MCA/MR) syndrome with variable expression, making diagnosis of mild cases difficult. The most consistent manifestations appear to be the characteristic face, which can be subtle in children who are mildly affected [Ireland and Burn, 1991: Twelfth Annual David W. Smith Workshop on Malformations and Morphogenesis]. Other aspects of the syndrome include variable degrees of mental retardation, growth retardation, structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…This study adds to the growing literature suggesting that a functional analysis-based approach to assessment and treatment that is the hallmark of applied behavior analysis can be highly effective in reducing severe behavior problems in individuals with specific genetic syndromes-for FXS as demonstrated in the current study; and for Prader-Willi (Stokes & Luiselli, 2009), Angelman (Kahng, Iwata, & Thompson, 2000), Cornelia de Lange (Bay et al, 1993), and Rett (Roane et al, 2001) syndromes. Collectively, these findings suggest that regardless of whether IDD is of idiopathic or genetic origin, functionbased interventions may be applied prior to pharmacological treatments when a specific behavioral function is identified, or may be applied in conjunction with pharmacological or other interventions if behavioral treatment alone is insufficient to reduce targeted problem behaviors (e.g., Hagopian & Caruso-Anderson, 2010).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This study adds to the growing literature suggesting that a functional analysis-based approach to assessment and treatment that is the hallmark of applied behavior analysis can be highly effective in reducing severe behavior problems in individuals with specific genetic syndromes-for FXS as demonstrated in the current study; and for Prader-Willi (Stokes & Luiselli, 2009), Angelman (Kahng, Iwata, & Thompson, 2000), Cornelia de Lange (Bay et al, 1993), and Rett (Roane et al, 2001) syndromes. Collectively, these findings suggest that regardless of whether IDD is of idiopathic or genetic origin, functionbased interventions may be applied prior to pharmacological treatments when a specific behavioral function is identified, or may be applied in conjunction with pharmacological or other interventions if behavioral treatment alone is insufficient to reduce targeted problem behaviors (e.g., Hagopian & Caruso-Anderson, 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Commonly identified consequences that reinforce and maintain problem behavior in persons with IDD include provision of adult attention, access to tangible items, and escape from non-preferred tasks (Iwata et al, 1994a,b); however, a number of other functions for problem behavior have been identified (Lancioni, Singh, O'Reilly, Sigafoos, & Didden, 2012;Schlichenmeyer, Roscoe, Rooker, Wheeler, & Dube, 2013). Studies reporting on the functional analysis of problem behavior have included subpopulations of IDD such as individuals with ASD (Love, Carr, & LeBlanc, 2009;O'Reilly et al, 2010); prenatal drug exposure (Kurtz, Chin, Rush, & Dixon, 2008); and genetic disorders such as Angelman (Strachan et al, 2009), Cornelia de Lange (Bay, Mauk, Radcliffe, & Kaplan, 1993), Prader-Willi (Hall, Hustyi, Chui, & Hammond, 2014), Rett (Roane, Piazza, Sgro, Volkert, & Anderson, 2001), Soto (Harding et al, 2001), and Williams syndromes (O'Reilly, Lacey, & Lancioni, 2000).…”
mentioning
confidence: 99%
“…Mutations in the adenylosuccinate lyase gene on chromosome 22q13.1-q13.2 have been reported in three sibs with autism [Stone et al, 1992], but not in a follow-up study of 119 patients with autism [Fon et al, 1993]. Finally, the appearance of autism in a small number of patients with various other genetic disorders (Fragile X syndrome, Rett syndrome, Goldberg-Shprintzen syndrome, Asperger syndrome, Brachmann-deLange syndrome, hypomelanosis of Ito, Joubert syndrome, neurofibromatosis, phenylketonuria, and tuberous sclerosis) is consistent with a genetic cause for autism and the potential involvement of a large number of genes in the development of language and social skills [Akefeldt and Gillberg, 1991;Annerén et al, 1995;Bay et al, 1993;Brown et al, 1986;Cohen et al, 1991;Folstein and Piven, 1991;Gillberg and Coleman, 1996;Holroyd et al, 1991;Hunt and Shepherd, 1993;Li et al, 1993;McKusick, 1994;Yomo et al, 1991]. This contention is further supported by sporadic reports describing a number of chromosome abnormalities, each of which has been seen in only one or a small number of patients with autism (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that CdLS is associated with autism spectrum disorder like impairments including poor expressive communication skills, social deficits, repetitive behaviours and a preference for rigid routines (Bay, Mauk, Radcliffe & Kaplan, 1993;Beck, 1987;Goodban, 1993;Hyman, Oliver & Hall, 2002;Johnson et al, 1976;Sarimski, 1997). Several studies have reported a heightened probability of autism in affected individuals.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Three separate studies have demonstrated the effect of environmental variables such as adult attention on the expression of self-injury and the effectiveness of behavioural treatment programmes in reducing the self-injury shown by three children with CdLS (Bay et al, 1993;Menolascino, McGee & Swanson, 1982;Singh & Pullman, 1979). The data from these three studies support the notion that self-injury in individuals with CdLS can be Detailed observations of individuals with CdLS have shown that those who self-injure may seek restraint and that distress is evident when physical restraints are removed (Dosseter et al, 2001;Shear, Nyhan, Kirman & Stern, 1971).…”
Section: Self Injurious Behaviourmentioning
confidence: 99%